2013
DOI: 10.14790/ijams.5.25
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Production Planning Using the Ranked Positional Weight Technique and Bayesian Estimation

Abstract: In recent years, almost every manufacturing site has been supported by a lot of part-time, temporary, or mid-career personnel, given the poor state of the economies all over the world. However, expert managers of front-line workers have to design more complex methods of production planning, when urgent orders due to uncertain elements like a disaster are taken into consideration. Therefore, this paper proposes a sustainable production planning model using an inference methodology. The method was suggested by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…On the other hand, it is seen that the propagation of breaking will greatly influence it. An example of Kataoka et al [8] is shown in Figure 2. The thick frame shows some observation points and the wavy frame shows some force points added to a building.…”
Section: Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, it is seen that the propagation of breaking will greatly influence it. An example of Kataoka et al [8] is shown in Figure 2. The thick frame shows some observation points and the wavy frame shows some force points added to a building.…”
Section: Modelingmentioning
confidence: 99%
“…Figure 2. Example of structural failure [8] In this paper, the concept of a sustainable production planning model is adopted to a comprehensive analysis as shown in Figure 3. Because of the prior job training, it is not easy to move work elements to another production Takayuki KATAOKA, Katumi MOEIKAWA , Katsuhiko TAKAHASHI International Journal of Japan Association for Management Systems process.…”
Section: Modelingmentioning
confidence: 99%
See 3 more Smart Citations